The author's guide to murder : a novel - Williams, Beatriz; Willig, Lauren; White, Karen (Karen S.) (William Morrow, an imprint of HarperCollinsPublishers, 2024)
At Castle Kinloch in the Scottish Highlands, literary superstar Brett Saffron Presley is found dead under strange circumstances, leading Detective Chief Inspector Euan McIntosh to investigate three American novelists--each with their own motives and secrets--as he uncovers connections between Presley's murder and the castle's dark history.